2014
DOI: 10.1186/1471-2180-14-137
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus crispatus L1: high cell density cultivation and exopolysaccharide structure characterization to highlight potentially beneficial effects against vaginal pathogens

Abstract: BackgroundVaginal lactic acid bacteria defend the host against pathogens through a combination of competitive exclusion, competition for nutrients, production of antimicrobial substances and through the activation of the immune system. A new human isolate named Lactobacillus crispatus L1 was characterized in this work, and a preliminary evaluation of its probiotic potential is described together with a process to obtain a high productivity of viable biomass.ResultsIn a simulated digestion process 1.8⋅1010 cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 42 publications
5
57
0
Order By: Relevance
“…Impairment of C . albicans adhesion in response to lactobacilli has previously been reported [22, 23], and Oliveira et al [46] showed an impact of L . rhamnosus ATCC7469 on several virulence attributes such as proteinase and haemolytic activity, germ tube and biofilm formation.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Impairment of C . albicans adhesion in response to lactobacilli has previously been reported [22, 23], and Oliveira et al [46] showed an impact of L . rhamnosus ATCC7469 on several virulence attributes such as proteinase and haemolytic activity, germ tube and biofilm formation.…”
Section: Discussionmentioning
confidence: 91%
“…Previous studies addressing the mechanisms behind probiotic action on C . albicans explored the ability of probiotic bacteria to inhibit fungal growth [1821], to prevent adhesion [22, 23] or to influence anti-fungal immune responses [23, 24], respectively. Despite the numerous studies on probiotics, the mechanisms behind the beneficial effects of probiotics on human health and well-being are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, specimens of Senegalese sole farmed under high stocking density and receiving a diet supplemented with SpPdp11 showed a higher resistance to disease in comparison with fish fed the diet without the probiotic [67], and this higher resistance was related to important changes in the intestinal microbiota, such as the presence of L. fermentum only in fish fed the diet supplemented with the probiotic [43]. Strains of L. crispatus have been associated with the ability to exert competitive exclusion and antimicrobial against vaginal human pathogens [69e71], being proposed as potential vaginal probiotic [72]. On the other hand, some trains of L. gasseri and L. johnsonii have also shown probiotic characteristics such as immunomodulatory [73] and anti-infective [74e76].…”
Section: Discussionmentioning
confidence: 99%
“…HBD-2 was induced in the distal tubules in the loops of Henle and collecting ducts in pyelonephritic kidneys (Lehmann et al 2002). Higher levels of neutrophil α-defensins are detectable in the vagina during infections with Neisseria gonorrhoeae, Trichomonas vaginalis or Chlamydia trachomatis (Donnarumma et al 2014b). α and β-defensins are expressed in the male reproductive tracts of humans, distributed in epididymus and seminiferous tubules, in the germ cells, Leyding cells and Sertoli cells (Yamaguchi et al 2002) HBD-2 in the genitourinary epithelia protect from infections caused by Candida (Wiechuła et al 2007).…”
Section: Defensins and Genitourinary Tract Diseasementioning
confidence: 99%